The Effect Of Brainstorming Toward The Students’ Vocabulary In Writing - Ferrenika Anggraini; Ikhsanudin; Dewi Novita (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study investigates the effectiveness of brainstorming techniques in improving vocabulary use in writing among seventh-grade students at SMPN 26 Pontianak. Utilizing a quantitative preexperimental design, the research involved a sample of 31 students from Class VII C out of a population of 96 students. The study aimed to assess whether brainstorming sessions could enhance students' vocabulary skills in descriptive text writing. A pre-test was administered to evaluate the students' initial vocabulary proficiency, followed by a series of brainstorming sessions, and a post-test was conducted to measure any improvements. The results revealed a significant increase in students' vocabulary scores, with mean scores rising from 33.42 in the pre-test to 54.00 in the post-test. The effect size of 4.29 indicates a strong impact of brainstorming on vocabulary enhancement. These findings suggest that brainstorming is a highly effective pedagogical tool for fostering vocabulary development and improving writing quality. The study recommends the integration of brainstorming techniques into teaching practices and suggests further research into the long-term effects and potential adaptations of this approach in diverse educational contexts.